Land acquisition in indonesia and law no. 2 of 2012 - James Guild (Asian Development Bank Institute (ADBI), 2019)
This paper is a qualitative case study of two land acquisition cases highlighting the empirical effect of legal reforms on land use policy over time in Indonesia. Under the Suharto regime, land acquisition in the public interest was often coercive, with the government determining one-sided compensation and no recourse for appeal. The legal basis for this process was Presidential Decree 55/1993, which gave the provincial governor the ultimate authority to rule on the matter. A new legal framework for land acquisition, which the government enacted in 2012, redefined the basis on which the state could acquire land in the national interest. It imposed clear administrative procedures and deadlines on dispute resolution and land procurement, including a legal appeal process. Outcomes can still vary widely according to many variables, particularly the capacity of district court judges, but comparative analysis suggests that the law is moving Indonesia toward a more equitable policy framework.
Keywords: H13; K11; K40; 330; Indonesia; land use policy; land acquisition; infrastructure; legal reforms